On the true cost of living index - Γαμαλέτσος Θεόδωρος (SPOUDAI Journal of Economics and Business, 2005)
The purpose of this paper is to present true cost of living indices derived from specific expenditure systems, and specifically from the LES, GLES and DGLES systems. According to Frisch [2] index numbers are classified into two categories: "statistical" and "functional". The former are purely descriptive statistics without any direct theoretical underpinning, while the latter are based on a formal theory and a precise theoretical interpretation. Here we present the advantage of the true cost of living index compared to the Laspeyre (statistical) index. Going a step further we show the advantage of using "dynamic" true cost of living index instead of using a "static" one. Finally by using the DGLES model to construct a dynamic true cost of living index we introduce habit formation hypothesis and changes in relative prices into these indices.